Physiological response of pilots to the load of lower body negative pressure - Hanousek, J; Dosel, P; Cmiral, J; Petricek, J (Journal of gravitational physiology, 1997)
The Czech Air-Force prepares an introduction of a new generation of aircraft with high maneuvering possibilities. The possibility of making full use of the aircraft flight properties assumes sufficient pilot's +Gz tolerance and also its improvement during the new flight training system. The optimal method to achieve this purpose is the human centrifuge utilization. For the Czech Republic, the building or the renting of a human centrifuge for the pilot's selection is unfortunately very expensive. In our institute we are interested in the analysis of the possibilities of the lower body negative pressure (LBNP) technique for the basic pilot's selection with low level of +Gz tolerance, using the examination of the orthostatic cardiovascular reactions of the pilot's organism.
Keywords: Lower Body Negative Pressure; Plethysmography; ozbrojené síly; abdominální dekomprese; hypergravitace; Hypergravity; výběr pracovníků; lidé; Military Personnel; krevní tlak; srdeční frekvence; Aerospace Medicine; Czech Republic; pletysmografie; Aircraft; letadla; Česká republika; letecké a kosmické lékařství; Blood Pressure; Heart Rate; Personnel Selection; Humans